Evolution of mechanical properties of flexible epoxy adhesives under cyclic loading and its effects on composite hybrid bolted/bonded joint design. (1st April 2018) - Lim, Gyu-Hyeong; Bodjona, Kobye; Raju, Karthik Prasanna; Fielding, Sean; Romanov, Valentin; Lessard, Larry
Abstract: Though aircraft joints conventionally employ either mechanical fastening or adhesive bonding, the hybrid bolted/bonded joint has recently appeared as an alternative with possible superior performance. A key aspect of the hybrid joint design is the load-sharing between the bolts and the bond, and performance can benefit from using a flexible adhesive. While the static properties of flexible epoxy adhesives are covered in the literature, the properties under cyclic loading are not fully understood. This study investigates the mechanical properties of flexible epoxy adhesives under cyclic loading and the corresponding effect on composite hybrid joints. This study is twofold. First, cyclic tensile tests on the bulk adhesive investigate the evolution of the adhesive stress/strain. The results show that the modulus and yield stress progressively decrease due to the accumulation of plastic deformation. As the load cycles continue, the stress/strain response converges limiting this accumulation. Subsequently, cyclic tension-tension tests are performed on hybrid joints. Attributed to the aforementioned behaviour of the adhesive properties, the bolt load-sharing is observed to progressively increase until a convergence is reached. This paper provides the understanding on the evolution of the mechanical properties of flexible adhesives under cyclic loading and further confirms their potential in hybrid joint applications.